2015
DOI: 10.1007/s11356-015-4830-y
|View full text |Cite
|
Sign up to set email alerts
|

Variation of phytoplankton functional groups modulated by hydraulic controls in Hongze Lake, China

Abstract: Hongze Lake is a large, shallow, polymictic, eutrophic lake in the eastern China. Phytoplankton functional groups in this lake were investigated from March 2011 to February 2013, and a comparison was made between the eastern, western, and northern regions. The lake shows strong fluctuations in water level caused by monsoon rains and regular hydraulic controls. By application of the phytoplankton functional group approach, this study aims to investigate the spatial and temporal dynamics and analyze their influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Most mountain lakes are oligotrophic and over a season, planktonic organisms experi ence a range of dynamic changes in resource availability at different temporal and spatial scales due to seasonality and mixing regimes. It has also been reported that increasing climate change impacts and an thropogenic activities conduct changes in resource availability and therefore have the potential to profoundly change planktonic commu nities (Berger et al, 2014;Gruner et al, 2017;Tian et al, 2015). Plankton variability may therefore also be an important indicator of change (Winder and Sommer, 2012), but we need to better understand the in herent natural variability of plankton in order to make future predic tions of the global change impact on aquatic ecosystem functioning (Chang et al, 2011;Ciszewski et al, 2013;Winder and Sommer, 2012).…”
Section: Human Disturbance and Food Web Dynamicsmentioning
confidence: 99%
“…Most mountain lakes are oligotrophic and over a season, planktonic organisms experi ence a range of dynamic changes in resource availability at different temporal and spatial scales due to seasonality and mixing regimes. It has also been reported that increasing climate change impacts and an thropogenic activities conduct changes in resource availability and therefore have the potential to profoundly change planktonic commu nities (Berger et al, 2014;Gruner et al, 2017;Tian et al, 2015). Plankton variability may therefore also be an important indicator of change (Winder and Sommer, 2012), but we need to better understand the in herent natural variability of plankton in order to make future predic tions of the global change impact on aquatic ecosystem functioning (Chang et al, 2011;Ciszewski et al, 2013;Winder and Sommer, 2012).…”
Section: Human Disturbance and Food Web Dynamicsmentioning
confidence: 99%
“…A good prediction of the water level is mandatory for tackling the water crisis and developing efficient emergency plans (Kozhevnikova & Shveikina, 2014). Water level fluctuations, caused by monsoonal climate and artificial drawdown can alter the hydrological conditions and influence light and nutrient availability, influencing phytoplankton succession (Tian et al 2015). The decrease in water level can indirectly affect the physical-chemical and biological characteristics of freshwater bodies, mainly through mixing enhancement (Valdespino-Castillo et al 2014).…”
Section: Model Performance For Water Balance and Water Temperaturementioning
confidence: 99%
“…In its current form, the PFG approach uses more than 40 categories according to the sensitivities and tolerances of representative taxa, identified by alphanumeric codes (Padisa´k et al, 2009;Salmaso et al, 2014). In the past decade, the PFG approach has provided important information for understanding the dynamics of phytoplankton communities and has been successfully applied in temperate (Huszar et al, 2003;Leita˜o et al, 2003;Tian et al, 2015), subtropical (Becker et al, 2009;Souza et al, 2016;Xiao et al, 2011), and tropical (Costa et al, 2009;Gebrehiwot et al, 2017;Rodrigues et al, 2017) regions.…”
Section: Introductionmentioning
confidence: 99%